PENGARUH PENGGUNAAN KONSENTRASI AIR KELAPA MUDA PADA PENGENCER NACL FISIOLOGIS TERHADAP MOTILITAS DAN MORTALITAS SPERMATOZOA IKAN TAWES ( Puntius javanicus) - Farah Diana; Muhammad Rizal; Dewi Mariani (Universitas Teuku Umar, 2015)
This study aims to knowing influence using cocentration of coconut water in physiology of NaCl dilution toquality of spermatozoa of Puntius javanicus. This research was counducted at Meunasah Krueng Village, Beutong Subdistrict, Nagan Raya District from 18th – 20th May 2015. Thecompletely randomized design with 5 treatmentand 3 replication was used for this study. Sample was saved in refrigerator (3 days) with temperature 4oC and it is oberved sample quality and data was collected in daily. Result of the research show water coconut concentration (7%) or in treatment 4th (P4) giving result for best quality of spermatozoa, where motility index average of spermatozoa is up to 80,55%, viability value of spermatozoa is up to 65,88%. In addtion, coconut water in in physiology of NaCl dilution have been affecting to spermatozoa quality of Puntius javanicus.